Generation of histo-anatomically representative models of the individual heart: tools and application. - Plank, G; Burton, R; Hales, P; Bishop, M; Mansoori, T; Bernabeu, M; Garny, A; Prassl, A; Bollensdorff, C; Mason, F; Mahmood, F; Rodriguez, B; et al. (2009)
This paper presents methods to build histo-anatomically detailed individualized cardiac models. The models are based on high-resolution three-dimensional anatomical and/or diffusion tensor magnetic resonance images, combined with serial histological sectioning data, and are used to investigate individualized cardiac function. The current state of the art is reviewed, and its limitations are discussed. We assess the challenges associated with the generation of histo-anatomically representative individualized in silico models of the heart. The entire processing pipeline including image acquisition, image processing, mesh generation, model set-up and execution of computer simulations, and the underlying methods are described. The multifaceted challenges associated with these goals are highlighted, suitable solutions are proposed, and an important application of developed high-resolution structure-function models in elucidating the effect of individual structural heterogeneity upon wavefront dynamics is demonstrated.